Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To convert the given equation from point-slope form to slope-intercept form, we need to simplify the equation step by step.
Given equation:
[tex]\[ y - 2 = 3(x + 1) \][/tex]
1. Distribute the 3 on the right side:
[tex]\[ y - 2 = 3 \cdot x + 3 \][/tex]
2. Simplify the equation:
[tex]\[ y - 2 = 3x + 3 \][/tex]
3. Add 2 to both sides to solve for \( y \):
[tex]\[ y = 3x + 3 + 2 \][/tex]
4. Combine like terms:
[tex]\[ y = 3x + 5 \][/tex]
So, the slope-intercept form of the equation is:
[tex]\[ y = 3x + 5 \][/tex]
Therefore, the correct option is:
[tex]\[ y = 3x + 5 \][/tex]
Given equation:
[tex]\[ y - 2 = 3(x + 1) \][/tex]
1. Distribute the 3 on the right side:
[tex]\[ y - 2 = 3 \cdot x + 3 \][/tex]
2. Simplify the equation:
[tex]\[ y - 2 = 3x + 3 \][/tex]
3. Add 2 to both sides to solve for \( y \):
[tex]\[ y = 3x + 3 + 2 \][/tex]
4. Combine like terms:
[tex]\[ y = 3x + 5 \][/tex]
So, the slope-intercept form of the equation is:
[tex]\[ y = 3x + 5 \][/tex]
Therefore, the correct option is:
[tex]\[ y = 3x + 5 \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.